Spatial and Temporal Distribution of Information Processing in the Human Dorsal Anterior Cingulate Cortex - Keogh, Conor; Deli, Alceste; Zand, Amir Puyan Divanbeighi; Zorman, Mark Jernej; Boccard-Binet, Sandra G.; Parrott, Matthew; Sigalas, Charalampos; Weiss, Alexander R.; Stein, John Frederick; FitzGerald, James J.; Aziz, Tipu Z.; Green, Alexander L.; et al. (Frontiers in Human Neuroscience, 2022)
The dorsal anterior cingulate cortex is a key node in the human salience network. It has been ascribed motor, pain-processing and affective functions. However, the dynamics of information flow in this complex region and how it responds to inputs remain unclear and are difficult to study using non-invasive electrophysiology. The area is targeted by neurosurgery to treat neuropathic pain. During deep brain stimulation surgery, we recorded local field potentials from this region in humans during a decision-making task requiring motor output. We investigated the spatial and temporal distribution of information flow within the dorsal anterior cingulate cortex. We demonstrate the existence of a distributed network within the anterior cingulate cortex where discrete nodes demonstrate directed communication following inputs. We show that this network anticipates and responds to the valence of feedback to actions. We further show that these network dynamics adapt following learning. Our results provide evidence for the integration of learning and the response to feedback in a key cognitive region.